Revolutionary Women and Daily Resistance. Reflections on Feminist Memory Practices in Chile (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In order to reflect on the relationship between gender and memory from a feminist perspective, memory practices are addressed as gendered and gendering processes rearticulating past and present. In the article, two types of memories of the Chilean dicta- torship are addressed: memories of women who recognize themselves as revolutionaries and combatants, in this case women who participated in armed resistance and / or were political prisoners, and memories of women who remember everyday forms of resistance, which have often been made invisible by hegemonic narratives focused on violent confrontations between men. These memories reveal different types of resistance practiced by women, contributing to the problematization of dominant androcentric memories of the Chilean dictatorship.
Keywords: memory, gender, resistance, Chilee